TRC120038, a Novel Dual AT(1)/ET(A) Receptor Blocker for Control of Hypertension, Diabetic Nephropathy, and Cardiomyopathy in ob-ZSF1 Rats - Mohanan, Anookh (SAGE-Hindawi Access to Research, 2011)
In hypertensive subjects, angiotensin II and endothelin participate in a manner involving closely interwoven pathways in increasing blood pressure (BP) and inducing end organ damage. The primary objective of this study was to determine the effect of TRC120038, a novel dual AT(1)/ET(A) receptor blocker on BP, in obese Zucker spontaneously hypertensive fatty rats (ob-ZSF1), an animal model of moderate hypertension, diabetes with progressive renal and cardiac dysfunction. Ob-ZSF1 rats loaded with 0.5% salt were treated with TRC120038 (11.8 mg/kg bid.) or candesartan cilexetil (0.3 mg/kg od.) or vehicle control. Blood pressure (by radio-telemetry) and renal functional markers were monitored throughout the study. Cardiac function was assessed terminally by pressure volume catheter. Markers for renal dysfunction were measured and changes were evaluated histopathologically. TRC120038 showed greater fall in both systolic and diastolic BP in comparison to candesartan at its maximum antihypertensive dose. TRC120038 also reduced the severity of renal dysfunction and preserved cardiac function in ob-ZSF1 rat.